Analisis Pembelajaran Tematik Berbasis Kecerdasan Komunikasi Siswa Sekolah Dasar - Nur Awalia; Angela Samosir (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to describe thematic learning based on communication intelligence of elementary school students. The research method used is descriptive qualitative research method, with pre-field, field, and data analysis steps. The data sources were the fifth grade teacher and all fifth grade students of SDN 013 Rambah, totaling 25 students consisting of 12 male students and 13 female students. Data collection techniques used are documentation, observation, and interviews. The research instrument used was teacher observation sheets, student observation sheets, and interview guidelines. The data analysis technique was carried out by qualitative data analysis techniques. The results showed that the thematic learning based on communication intelligence of elementary school students was in the medium category. The conclusion of this study is that thematic learning based on student communication intelligence is classified as moderate because teachers who apply thematic learning in elementary schools implement thematic learning well. Teachers must pay more attention to every intelligence possessed by each student and teachers must apply learning methods that are in accordance with these intelligences.